Strategi Perencanaan Dan Pengembangan Industri Pariwisata Dengan Menggunakan Metode Swot Dan Qspm (Studi Kasus Kecamatan Leitimur Selatan Kota Ambon) - FRETES, Richard A.de; Santoso, Purnomo B.; Soenoko, Rudy; Astuti, Murty (Jurnal Rekayasa Mesin, 2013)
Problems faced by South Leitimur Ambon District was had a lot of undeveloped tourism potential developed as a tourist attraction that makes this region as a tourist destination areas (DTW). Thus, the strategic planning and development of tourism industry must be oriented to the development of tourism potential possessed by considering the problems faced, the economy was able to increase the income of local communities. This research is a type of qualitative research data collection techniques through direct observation (observation), indepth interviews (depth interviews), distributing questionnaires (questionnaire) and the study of literature. Presentation of analysis done formally (in tabular form) or informal (narrative). The method used is the method of SWOT and QSPM form, data analysis performed by Internal External Factors, IE matrix analysis, SWOT analysis and research QSPM. The result of analysis is to show the position of tourism in the district of South Leitimur with a market penetration strategy and product development, strategic SWOT analysis of the SO, ST, WO and WT, QSPM analysis shows that the strategy should be prioritized first Product development is a 15.550 total of TAS, TAS total Progressive strategy II 14.050, III 13.350 TAS total market penetration and IV diversification strategy of the TAS total of 13,00. To develop the sub-region South Leitimur based on the results of the analysis and strategic issues are obtained, it will be obtained or performed the following programs: Tourism Potential Collection owned, Development of tourism potential, the potential increase in tourism, infrastructure improvement, increase the quality of human resources , Increasing and strengthening management systems and increase welfare.Keywords: tourism potential, strategic planning, analysis and swot analysis qspm.